Znaczenie kategorii „zaufanie” oraz „ryzyko” dla współczesnej młodzieży - Peret-Drążewska, Paulina (Kultura-Społeczeństwo-Edukacja, 2021)
This article presents theoretical considerations on the category of trust and risk as constructs particularly important for an individual participating in contemporary socio-cultural realities, especially for young people. Theoretical analyses of the concepts of trust and risk are presented. The basis for these analyses was the concept of the sense of ontological security set in the context of contemporary socio-cultural conditions and globalization processes. Trust and risk are categories of particular importance to young people at present, which is why this age group was emphasized in the theoretical analyses undertaken.